Determining the isotopic composition of elements from the electrospray ionization mass spectra of their chemical species. Issue 4 (11th March 2021) - Blanchard, E.; Paredes, E.; Rincel, A.; Nonell, A.; Chartier, F.; Bresson, C.
Abstract : Isotopic composition of elements was determined by applying a deconvolution method that we developed to electrospray mass spectra of the associated chemical species. Abstract : Electrospray ionization mass spectrometry (ESIMS) is traditionally used to analyse organic molecules, but can also be used to carry out elemental speciation studies. The challenge is here to determine the isotopic composition of elements contained in chemical species by this technique, in addition to their quantification and structural characterisation. In the present work, we determined by ESIMS the isotope ratios of samarium (Sm) and neodymium (Nd) involved in complexes containing polyaminocarboxylic acids, namely EDTA and DTPA. To this end, we developed a user-friendly deconvolution method to remove the ligand isotopic contributions from the abundance ratios measured in the ESI mass spectra of the complexes, and thus obtaining the isotopic composition of the free lanthanides. By applying the deconvolution method to EDTA complexes containing natural and enriched samarium, we obtained the nat Sm and the 147–149 Sm isotopic composition directly from the mass spectra of the chemical species recorded by commercial ESI mass spectrometers, equipped with a triple quadrupole analyser (QqQ) or a linear ion trap (LIT). The isotopic composition of nat Sm and 147–149 Sm were determined with a trueness better than 3.5% and 2% by ESI-QqQ-MS and better than 1% and 2% by ESI-LIT-MS, with a repeatability globally better than 3% at k = 2, for isotopes of relative abundances greater than 1% in samples. This method was successfully applied to determine nat Nd and nat Sm isotopic compositions from nat Nd–EDTA, nat Sm–DTPA and nat Nd–DTPA mass spectra.